MOG Antibody-Associated Disorders Following SARS-CoV-2 Vaccination: A Case Report and Literature Review - Matsumoto, Yuki; Ohyama, Ayane; Kubota, Takafumi; Ikeda, Kensuke; Kaneko, Kimihiko; Takai, Yoshiki; Warita, Hitoshi; Takahashi, Toshiyuki; Misu, Tatsuro; Aoki, Masashi (Frontiers in Neurology, 2022)
Background: Myelin oligodendrocyte glycoprotein antibody associated disorder (MOGAD) is a newly identified autoimmune demyelinating disorder, often associated with acute disseminated encephalomyelitis, usually in post-infectious or post-vaccination situation. Here we report a case of MOGAD after the mRNA SARS-CoV-2 vaccination. Case presentation: A previously healthy 68-year old woman presented to our department due to gradually worsening numbness on right side of her face two weeks after second dose of mRNA-1273 vaccination. Her brain MRI showed right cerebellar peduncle lesion with gadolinium enhancement; typical finding of MOGAD. Neurological examination revealed paresthesia on her right V2 and V3 area. Other neurological examination was unremarkable. Laboratory workup showed a positivity of MOG-IgG in her serum by live cell-based assay and oligoclonal bands in cerebrospinal fluid (CSF). Her serum test results for cytoplasmic-antineutrophil cytoplasmic antibody, perinuclear-cytoplasmic-antineutrophil cytoplasmic antibody, GQ1b-antibody and aquaporin-4 antibody (AQP4-IgG) were all negative. Soluble interleukin (IL)-2 receptor in serum, IL-6 in CSF, skin prick test, angiotensin converting enzyme test were all unremarkable. She was diagnosed with MOGAD after mRNA SARS-CoV-2 vaccination. Her symptoms were improved and her cerebellar peduncle lesion shrunk slightly without gadolinium enhancement after two courses of intravenous methylprednisolone treatment. So far, there are only 3 cases of monophasic MOGAD following SARS-CoV-2 vaccination, including ChAdOx1 nCOV-19 and mRNA 1273, but the prognosis is generally well similar to the other typical MOGAD cases. Conclusion: MOG antibody is relatively rare in post-Covid19-vaccine demyelinating diseases, but MOGAD should be considered in patients with CNS demyelinating disease after SARS-CoV-2 vaccination.